3-D super-resolution ultrasound (SR-US) imaging using a 2-D sparse array with high volumetric imaging rate - Harput,S; Christensen-Jeffries,K; Brown,J; Zhu,J; Zhang,G; Leow,CH; Toulemonde,M; Ramalli,A; Boni,E; Tortoli,P; Eckersley,RJ; Dunsby,C; et al. (IEEE, 2018)
Super-resolution ultrasound imaging has been sofar achieved in 3-D by mechanically scanning a volume witha linear probe, by co-aligning multiple linear probes, by usingmultiplexed 3-D clinical ultrasound systems, or by using 3-D ultrasound research systems. In this study, a 2-D sparsearray was designed with 512 elements according to a density-tapered 2-D spiral layout and optimized to reduce the sidelobesof the transmitted beam profile. High frame rate volumetricimaging with compounded plane waves was performed usingtwo synchronized ULA-OP256 systems. Localization-based 3-Dsuper-resolution images of two touching sub-wavelength tubeswere generated from a 120 second acquisition.